EFISIENSI SISTEM PENYIMPANAN OBAT DI BEBERAPA PUSKESMAS DAERAH YOGYAKARTA - Rosita, Melia Eka; Fajri, M. Alif; Nilansari, Anis Febri (Jurnal Riset Kefarmasian Indonesia, 2024)
Medicine storage is an activity to ensure that the medicines received are placed in a place that is considered safe, which includes 3 elements, namely spatial planning and preparation of the medicine warehouse, safeguarding the quality of medicines, and recording medicine stock. Medication storage errors can cause drug shortages, losses due to lost or damaged and expired drugs, and also result in the potency of a drug decreasing which then results in it being ineffective if consumed by the patient. The aim of this research is to determine the suitability of drug storage and determine the efficiency of drug storage at the Sleman Health Center, Yogyakarta City and Bantul. This research is non-experimental research, with a descriptive qualitative research type and design. The results of research on drug storage in the three community health centers meet the standards in the "Very Good" category based on the Pharmaceutical Management Training Materials in Community Health Centers published by the Ministry of Health in 2010, as well as technical instructions for pharmaceutical service standards in Community Health Centers from the Ministry of Health in 2019. Results of drug storage efficiency Value The Turn Over Ratio (TOR) at the Sleman Community Health Center was 10.87 times, the Yogyakarta City Health Center 9.55 times and the Bantul Community Health Center 11.33 times. The percentage of expired and damaged medicines at the Sleman Community Health Center was 5.33%, Yogyakarta City Health Center 7.5% and Bantul Community Health Center 3.63%. The percentage of dead stock medicines at the Sleman Community Health Center is 9.38%, the Yogyakarta City Health Center is 10.12% and the Bantul Community Health Center is 1.35%.